Functional Constipation in Children: overview and new outcomes - Stępień, Kamila; Przygoda, Maria; Śnieżna, Joanna; Trestka, Gabriela; Adamczyk, Sabina; Zelik, Urszula; Dziewic, Jakub; Florczak, Wojciech; Domino, Wiktoria; Włodyka, Jagienka; et al. (Quality in Sport, 2025)
Functional constipation (FC) is a prevalent gastrointestinal disorder in children, characterized by infrequent, difficult, or painful bowel movements without an identifiable organic cause. This review provides an overview of functional constipation in children, discussing its epidemiology, pathophysiology, clinical presentation, diagnostic approach, and management strategies. FC affects approximately 5-30% of children, with risk factors including dietary habits, psychosocial stressors, and family history. The pathophysiology involves colonic hypomotility, rectal hyposensitivity, and behavioral factors, often compounded by pelvic floor dysfunction. Diagnosis is primarily clinical, based on Rome IV criteria, with further testing considered in atypical cases. Management includes dietary modifications, behavioral interventions, pharmacotherapy, and, in some cases, biofeedback therapy. Long-term outcomes are generally favorable with appropriate treatment, although relapse is common, emphasizing the need for sustained management. Functional constipation significantly impacts a child’s quality of life, affecting both physical and emotional well-being. A multidisciplinary approach is essential for effective treatment, addressing both physiological and psychological aspects to optimize long-term health outcomes for children with FC.